The moderating effect of the interaction between joint audit and accounting conservatism on the association between corporate governance and corporate performance - Ahmed Elmashtawy; Mohd Hassan Che Haat; Shahnaz Ismail; Faozi A. Almaqtari (Cogent Business & Management, 2024)
The study's purpose is to examine the effects of corporate governance (CG) mechanisms on corporate performance (CP) and the moderating effect of the interaction between joint audit (JA) and accounting conservatism on this relationship in Egypt. From 2016 through 2020, the sample consisted of 61 non-financial Egyptian corporations listed. Panel data analysis with fixed-effect models was utilized to estimate the findings. The findings reveal that CG mechanisms as individual variables and CG index have a significant effect on CP by market- and accounting-based measures. The results also exhibit that the interaction between JA and accounting conservatism moderates and strengthens the relationship between the CG index and CP. The study's unique contributions materialize in combining individual relationships into a comprehensive model. The model portrays the interaction between JA and accounting conservatism as a moderator in the relationship between CG mechanisms and CP. Furthermore, the study examines market- and accounting-based CP. The findings corroborate the literature and theoretical foundations of CG in emerging markets and focus on effective mechanisms for CG in various economic sectors. This study provides several practical implications for policymakers, auditors, corporations, shareholders, investors and practitioners, especially in emerging markets.The interplay among corporate governance, joint audit, and accounting conservatism plays a critical role in a company's performance. Nonetheless, the literature offering a comprehensive exploration of these interrelationships remains limited. Hence, our paper's unique contributions materialize by combining individual relationships into a comprehensive model. The comprehensive model portrays the interaction between joint audit and accounting conservatism as a moderator in the relationship between corporate governance mechanisms (through a compound index for corporate governance) and corporate performance (through market- and accounting-based corporate performance). The sample consists of 305 firm-year observations spanning the Egyptian context from 2016 to 2020. Panel data analysis with fixed-effect models is utilized to estimate the findings. Supplementary analyses are performed to assess the study findings' robustness and ensure that the main findings are robust with different measurements.
Keywords: G34; M42; 650; Corporate performance; corporate governance; joint audit; accounting conservatism; Egypt